2020
DOI: 10.1002/ijfe.1853
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of FDI in France: Role of transport infrastructure, education, financial development and energy consumption

Abstract: This article explores the effect of education and transportation infrastructure on foreign direct investment for the French economy over the period of 1965–2017. Economic growth, financial development and electricity consumption are also considered as additional determinants of foreign direct investment. In so doing, the SOR unit root test is applied in order to examine unit root properties of variables in the presence of sharp and smooth structural breaks in the series. To examine the presence of cointegratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 86 publications
3
13
0
Order By: Relevance
“…The available literatures indicate that there is no mutual consent upon the economic determinants of foreign direct investment (Bimal, 2017;Nkoa, 2018;Camarero, Montolio, & Tamarit, 2020;Hanh, 2020;Minhaj-ud-Din, Azam & Tariq, 2020;Shahbaz et al, 2021). Similarly, we do not find any literature that has explicitly investigated this issue for the five South Asian economies.…”
Section: Literature Reviewmentioning
confidence: 55%
See 1 more Smart Citation
“…The available literatures indicate that there is no mutual consent upon the economic determinants of foreign direct investment (Bimal, 2017;Nkoa, 2018;Camarero, Montolio, & Tamarit, 2020;Hanh, 2020;Minhaj-ud-Din, Azam & Tariq, 2020;Shahbaz et al, 2021). Similarly, we do not find any literature that has explicitly investigated this issue for the five South Asian economies.…”
Section: Literature Reviewmentioning
confidence: 55%
“…However, economic growth was found essential for bringing stability in the inflow of FDI. Shahbaz al. (2021) found that high-quality growth in the transportation, education, and financial sector discourages the need for investment, and, hence, the inflow of FDI is reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has an impact on investments and the profitability of companies. Several empirical studies in this direction have shown that the quality of transport infrastructure improves investment (Khadaroo and Seetanah, 2010;Samir and Mefteh, 2020;Shahbaz et al, 2021) and hence economic growth (Bosede et al, 2013;Cigu et al, 2019).…”
Section: Theoretical Discussion Of How Infrastructure Development Could Affect Structural Changementioning
confidence: 99%
“…Hence, a positive effect of education on FDI inflows may be hypothesized. Moreover, the FMD is a vital determinant of the macroeconomic performance of any investment, including FDI inflows [23]. Increasing FMD may indicate a better economic environment, which may attract the FDI for economic incentives, large market size, and more comfortable financial transactions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they argued a need for quality education to comprehend the complementary relationship between education and FDI. Shahbaz et al [23] investigated the role of FMD and education on FDI in France, controlling some other important determinants using a period 1965-2017, and found that France's education and transport infrastructure have supported the FDI inflows. However, the effect of FMD was found negative on FDI.…”
Section: Introductionmentioning
confidence: 99%